78 Empiric versus entrained cavotricuspid isthmus line ablation in congenital heart disease: a single centre experience. (5th June 2017) - Sawhney, Vinit; McLellan, Alex; Perera, Dhanuka; Babra, Deshveer; Izquierdo, Dionisio; Schilling, Richard; Lambiase, Pier; Lowe, Martin; Ezzat, Vivienne
Abstract : Introduction: Catheter ablation for supraventricular tachycardia (SVT) in patients with congenital heart disease (CHD) is an important therapeutic option. Complex atrial substrate in this cohort makes atrial flutter (AFl) a common occurrence. However, induction of sustained tachycardia at the time of ablation is not always possible. We hypothesised that performing an empiric Cavotricuspid Isthmus CTI line ablation in case of non-inducibility of arrhythmia will lead to good outcomes. Long-term outcomes of empiric versus entrained CTI ablation in CHD patients with right-sided supraventricular arrhythmias were examined. Methods and results: 51 right-sided atrial flutter ablations in 49 patients from 2007–2015 were included. Data was analysed retrospectively. Medical records were reviewed and patients were contacted for follow-up. All patients with left sided arrhythmias were excluded. The mean age of the whole cohort was 43 years and 50% of the patients were men. Underlying aetiology included ASD (33.3%), VSD (19.6%), Fallot's tetralogy (15.6%), Ebstein's anomaly (3.9%), Fontan surgery (10%) and Mustard repair (17.6%). There was no significant difference in the right atrial sizes between the two groups. AFl was entrained in 34 patients whereas it was non-inducible/non-sustained in 17 patients. The latter had an empiric CTI line ablation. Of those in the entrained group, 3% had other atrial arrhythmias induced in addition to typical AFl. 51% of procedures were performed without a general anaesthetic. There were no procedural complications. There was no significant difference in the mean procedure and fluoroscopy times between the two groups (Empiric vs Entrain CTI; 176.5 vs 163.8 and 41.5 vs 30.5 min). After a mean follow-up of 21 months, arrhythmia-free survival was 71% versus 85% (p-value 0.21) in the empiric and entrained CTI ablation groups. Conclusion: Long-term outcomes after empiric and entrained CTI line ablation for AFl in patients with CHD are comparable. This is a safe and effective treatment option. In the case of non-inducibility of atrial flutter, an empiric CTI line ablation should be performed in this cohort.